Teaching journalism students how to tell Indigenous stories in an informed way: a work integrated learning approach. - Stewart, H.; Williams, M.; Cullen, T.; Johnston, Michelle; Phillips, G.; Mulligan, P.; Bowman, L.; Meadows, M. (Sage Publications, 2013)
Australian journalism schools are full of students who have never met an Aboriginal or Torres Strait Islander person and who do not know their history. Journalism educators are ill-equipped to redress this imbalance as the large majority are themselves non-Indigenous and many have had little or no experience with the coverage of Indigenous issues or knowledge of Indigenous affairs. Such a situation calls for educational approaches that can overcome these disadvantages and empower journalism graduates to move beyond the stereotypes that characterise the representation of Indigenous people in the mainstream media. This paper will explore three different courses in three Australian tertiary journalism education institutions who use Work Integrated Learning approaches to instil the cultural competencies necessary to encourage a more informed reporting of Indigenous issues. The findings from the three projects illustrate the importance of adopting a collaborative approach by industry, the Indigenous community and educators to encourage students’ commitment to quality journalism practices when covering Indigenous issues.